Preliminary analysis of dust effects on microwave propagation measured in Sudan - Elfatih, Elsheikh; Islam, Md. Rafiqul; Chebil, Jalel; Bashir, Saad Osman; Ismail, Ahmad Fadzil (2013)
Dust storms are meteorological phenomena which occur for a percentage of time in arid and semi arid areas especially at African Sahara and Middle East. Measurements at existing microwave links have showed dust storms can potentially result in serious attenuation in signal level especially at Ku band and higher frequencies with direct impact on telecommunications system performance. Only a limited amount of research has been carried out and the available data was very scarce. Few prediction models have been developed to estimate microwave signal attenuation during the dust storm based on scattering theory and approximation of dust properties. However, real dust storm is a complex phenomenon which is difficult to be described by theoretical physical or mathematical models [5-6]. In this paper, an evaluation of the existing attenuation prediction models has been done based on the measured dust storm properties and measured attenuation in Sudan.